2018
DOI: 10.1155/2018/5128626
|View full text |Cite
|
Sign up to set email alerts
|

The First Harmonic of Radial Pulse as an Early Predictor of Silent Coronary Artery Disease and Adverse Cardiac Events in Type 2 Diabetic Patients

Abstract: Background It has been reported that harmonics of radial pulse is related to coronary artery disease (CAD) in patients with type 2 diabetes mellitus (T2DM). It is still unclear whether or not the first harmonics of the radial pulse spectrum is an early independent predictor of silent coronary artery disease (SCAD) and adverse cardiac events (ACE). Objectives To measure the risk of SCAD in patients with T2DM and also to survey whether or not an increment of the first harmonic (C1) of the radial pulse increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Radial pulse waves were noninvasively measured by medical‐grade devices that had been found to be highly reproducible (Chang and Wang ), and the intra‐observer and inter‐observer reliabilities met the criteria for medical interpretation (Portney and Watkins ; Chang et al ). The standard operating procedures for environmental temperature control and radial pressure wave measurement were as described in previous studies (Chang et al , ). Before the measurement started, each patient was asked to rest for more than 5 min, keeping blood pressure as stable as possible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Radial pulse waves were noninvasively measured by medical‐grade devices that had been found to be highly reproducible (Chang and Wang ), and the intra‐observer and inter‐observer reliabilities met the criteria for medical interpretation (Portney and Watkins ; Chang et al ). The standard operating procedures for environmental temperature control and radial pressure wave measurement were as described in previous studies (Chang et al , ). Before the measurement started, each patient was asked to rest for more than 5 min, keeping blood pressure as stable as possible.…”
Section: Methodsmentioning
confidence: 99%
“…The endpoint of coronary artery disease was defined as a new diagnosis of single coronary artery stenosis (≥70%), multiple coronary stenoses (≥50%), and ischemic myocardium (≥10%) for further cardiac examination. Definition of nonfatal myocardial infarction, hospitalization for heart failure, and diagnosis of coronary artery stenosis was detailed in previous studies (Chang et al ). The secondary interest outcomes were the composite endpoints of the microvascular events, composed of the major adverse kidney events (composite endpoints of double serum creatinine, end‐stage renal disease, kidney failure, and renal cause of death), macroalbuminuria, retinopathy, and polyneuropathy.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies also reported the factor of atherosclerosis [30, 31], or increasing afterload [29] will increase the first harmonic impedance which is related to the increasing burden of heart muscle. Chang et al reported that screening for the C1 may improve the risk stratification of cardiac events and silent coronary artery disease in asymptomatic patients [32]. Hence, the first harmonic amplitude increment could be a noninvasive risk marker for cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…where Ω is the bandwidth of interest andP(ω) is an estimation of the energy-normalised power power of such signal. However, the relative power using ratios of harmonics is relevant and indeed contains known health information [35,[53][54][55]. In our work we will limit the number of harmonics to Nb H = 4 and we use the harmonic power ratios as features: H i,j = A H i /A H j for i, j = 0, .., Nb H with j > i.…”
Section: Feature Extractionmentioning
confidence: 99%